Impact of Demographic Factors on Risk Tolerance - Timilsina, Bharat (Journal of Kathmandu BernHardt College, 2026)
This study investigates the influence of demographic factors on Financial Risk Tolerance (FRT) among Nepalese investors, focusing on gender, marital status, income, education, age, and investment experience. Guided by behavioral finance theory, it employs a quantitative, cross-sectional design with data from 422 verified stock market participants across Nepal, collected through licensed brokerage firms and an online questionnaire. FRT was measured using the financial subscale of the Domain-Specific Risk-Taking (DOSPERT) scale (α = .81). Multiple and hierarchical regression analyses revealed that gender significantly influenced FRT, with male investors reporting higher tolerance, while marital status was insignificant. The interaction between income and education was significant, showing that higher education increased FRT even among low-income investors. Overall, demographic variables collectively predicted FRT, with education and the income–education interaction emerging as the strongest predictors. Findings highlight the role of socio-cultural and economic factors in shaping financial risk-taking, underscoring education as a key moderator of risk aversion. The study contributes to behavioral finance literature in emerging markets and offers insights for policymakers, educators, and financial institutions to foster inclusive investment behavior.